(untitled) (Fiep Bulletin - online, 2016)
Objective: to investigate the prevalence of Musculoskeletal disorders in a group of nurses. Method: an exploratory study with a quantitative approach conducted with 40 nurses (30% of the target population) who work at a public hospital in Paraíba where a survey was applied and analyzed through statistic methods. Results: there was predominance of female young adults, married, who work as service providers without tenure. The prevalence of painful symptoms reached 87,5% and the main symptoms were: were lumbago (29,4%,) neck pain (20,7%), pain in the ankles and feet (16,4%), backache (10,9%), shoulder pain (9,8%), knee pain (5,4%), pain in the hands and wrist (5,4%), pain in the thighs and arms (2%). Inadequate posture for prolonged periods was indicated as the main factor that causes the lesions, followed by excessive physical effort and working time. Conclusion: the results attained by this paper make us review the work conditions and reconsider feasible strategies to transform the current scenario of constant cases where professionals suffer from work related disorders from their duties as nurses.